Pilot-scale production of candied dehydrated jackfruit (Artocarpus heterophyllus Lam) - Villanueva, Daphne; De Leon, Sonia Y. (1985.)
The study was divided into three parts. The first was on the physical characterization of the local jackfruit (Artocarpus heterophyllus Lam.) variety particularly to determine the per cent edible portion from the whole fruit. The second was an evaluation of three methods of lumping for candied dehydrated jackfruit. Objective tests as well as sensory evaluation of the different product samples of candied dehydrated jackfruit syruped at 35-45°Bx; 35-55°Bx; and 35-65°Bx were undertaken. Statistical analyses of data showed that 35-65°Bx syruping yielded the most acceptable product described as slightly shriveled in appearance, golden yellow in color, having characteristic jackfruit aroma, moderate jackfruit flavor and a tender but firm texture. The mean rating for general acceptability was equivalent to like moderately. Finally, the technical considerations in the pilot-scale production of candied dehydrated jackfruit were studied in the third phase. Raw material specifications, in-process critical points, and proposed finished product specifications are presented.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Jackfruit, Candied; Fruit -- Processing